Allele and haplotype diversity of 12 X-STRs in Sardinia. (March 2018) - Robino, C.; Lacerenza, D.; Aneli, S.; Di Gaetano, C.; Matullo, G.; Robledo, R.; Calò, C.
Highlights: Diversity at four clusters of closely linked X-STR triplets was studied in Sardinia. Evidence of LD was detected in Sardinia within each linkage group. Genetic heterogeneity was seen for isolated, but not for open Sardinian populations. X-STR haplotype data for likelihood calculations in kinship testing are provided. Abstract: The analysis of clusters of tightly linked X-chromosome short tandem repeat (STR) markers can assist the interpretation of complex kinship cases. However, when linkage disequilibrium (LD) is present in the population of origin of tested individuals, haplotype rather than allele frequencies should be used in likelihood calculations. The diversity of twelve X-STRs arranged in four linkage groups (I: DXS10148-DXS10135-DXS8378; II: DXS7132-DXS10079-DXS10074; III: DXS10103-HPRTB-DXS10101; IV: DXS10146-DXS10134-DXS7423) was tested in a Sardinian population sample (n = 516) including three open populations from the Northern, Central and Southern part of the island, and three isolates (Benetutti, Desulo, Carloforte). Evidence of LD was detected in Sardinia within each linkage group. Significant differences in haplotype and allele frequency distribution of X-STR markers was seen between isolates and open populations, which on the contrary appeared highly homogeneous. The percentage of Sardinian haplotypes previously unobserved in a similar dataset compiled for the Italian population was: 76.3% (linkage group I), 61.3% (linkage group II), 54.1% (linkage group III), 58.9% (linkage group IV). Significant pairwise genetic differences were seen between mainland Italy, the three Sardinian isolates, and the open population of Southern Sardinia. The study confirms the presence of high levels and complex patterns of LD along the X chromosome in Sardinia, and provides population-specific haplotype data for biostatistical evaluation in kinship testing.